f " (x) = X^2 + X -1, f ' (0)=5, f (0)=10

First we need to determine f'(x) by calculating the integral of f''(x)

We know that:

f'(x) = intg f''(x)

==> f'(x) = intg (x^2 + x -1) dx

= x^3/3 + x^2/2 - x + C

==> f'(x) = (1/3)x^2 + (1/2)x^2 - x + C

Given that:

f'(0) = 5

==> f'(x) = (1/3)x^3 + (1/2)x^2 - x + 5

Now let us calculate f(x)"

We know that:

f(x) = intg f'(x)

= intg ((1/3)x^3 + (1/2)x^2 - x + 5) dx

= (1/3)x^4/4 + (1/2)x^3/3 - x^2/2 + 5x + C

= (1/12)x^4 + (1/6)x^3 - (1/2)x^2 + 5x + C

Given that:

f(0) = 10 ==> c = 10

**==> f(x) = (1/12)x^4 + (1/6)x^3 - (1/2)x^2 + 5x + 10**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now